2019
DOI: 10.2174/1389557519666190906120228
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Inhibitors against Botulinum Neurotoxins: 8-Hydroxyquinolines Hold Promise

Abstract: Botulinum neurotoxins (BoNTs) are the most toxic category A biological warfare agents. There is no therapeutics available for BoNT intoxication yet, necessitating the development of a medical countermeasure against these neurotoxins. The discovery of small molecule-based drugs has revolutionized in the last two decades resulting in the identification of several small molecule inhibitors of BoNTs. However, none progressed to clinical trials. 8-Hydroxyquinolines scaffold-based molecules are important ‘privileged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…For example, Crespy and coworkers [23] prepared pH-sensitive polymer conjugates from 8HQ, ethyl acrylate, and 2-mercaptoethanol, which could well be utilized in the corrosion protection of metal. Additionally, it has a broad prospect in pharmaceutical engineering [24][25][26][27][28][29][30]. Kljun et al [25] demonstrated the anticancer potential of organ ruthenium complexes of 8HQ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Crespy and coworkers [23] prepared pH-sensitive polymer conjugates from 8HQ, ethyl acrylate, and 2-mercaptoethanol, which could well be utilized in the corrosion protection of metal. Additionally, it has a broad prospect in pharmaceutical engineering [24][25][26][27][28][29][30]. Kljun et al [25] demonstrated the anticancer potential of organ ruthenium complexes of 8HQ.…”
Section: Introductionmentioning
confidence: 99%
“…Kljun et al [25] demonstrated the anticancer potential of organ ruthenium complexes of 8HQ. Chauhan et al [26] prepared a therapeutic agent for botulinum neurotoxins from 8HQ. Buchler et al [27] optimized the inhibitory effect of 8HQ inhibitors on catechol O-methyltransferase.…”
Section: Introductionmentioning
confidence: 99%